Role of Academia in Effective Implementation of Inclusive Education: Through Imparting Inclusive Teacher Training - Fauzia Khurshid, Shahid Farooq (JIE, 2024)
Present research was designed to determine the role of academia in effective implementation of inclusive education through teacher education programs. Main objectives of this research were to examine the scheme of studies developed by HEC for Teachers education program (B. ED B.S. ED) offered in the various private and public sector universities and degree awarding institutions with reference to inclusion of content on inclusive education and to examine the module of inclusive education in the course outlines of Teachers education program (B. ED B.S. ED) offered in the various private and public sector universities and degree awarding institutions, to examine the content on the inclusive education with reference to practical aspects of inclusive pedagogy, inclusive curriculum, assistive devices and inclusive assessment for diverse learners. Qualitative and quantitative approaches were used to get information about the phenomena.